2016
DOI: 10.1093/scan/nsw036
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in self-reported self-control predict successful emotion regulation

Abstract: Both self-control and emotion regulation enable individuals to adapt to external circumstances and social contexts, and both are assumed to rely on the overlapping neural resources. Here, we tested whether high self-reported self-control is related to successful emotion regulation on the behavioral and neural level. One hundred eight participants completed three self-control questionnaires and regulated their negative emotions during functional magnetic resonance imaging using reappraisal (distancing). Trait s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
76
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(87 citation statements)
references
References 105 publications
(144 reference statements)
9
76
0
2
Order By: Relevance
“…In some cases we can find inter-individual differences characterized by vary different stable habits for different individuals (e.g., the impulsive spendthrift vs. the miser) and in other cases we find intra-individual differences in behavior from one time to another, or from one decision domain to another. As suggested by our model and corroborating evidence, people facing decision dilemmas may differ in the degree to which they anticipate and are motivated by either of two conflicting utilities and the degree to which they experience and can regulate emotional consequences of past decisions [5], and perhaps because of sex differences affecting the perception of different emotions [149]. The conflicted goal approach of considering a DMs utility function may be even more important for understanding intra-individual differences revealed at 13 Soutschek and colleagues [59] have suggested that the brain regions underlying self-control mechanisms involved in individual decision dilemmas (e.g., trading off impulsive short vs. restrained long-term goals) are also underlying decisions in social dilemmas (e.g., trading off exploitative and individually beneficial vs. cooperative and mutually beneficial goals).…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…In some cases we can find inter-individual differences characterized by vary different stable habits for different individuals (e.g., the impulsive spendthrift vs. the miser) and in other cases we find intra-individual differences in behavior from one time to another, or from one decision domain to another. As suggested by our model and corroborating evidence, people facing decision dilemmas may differ in the degree to which they anticipate and are motivated by either of two conflicting utilities and the degree to which they experience and can regulate emotional consequences of past decisions [5], and perhaps because of sex differences affecting the perception of different emotions [149]. The conflicted goal approach of considering a DMs utility function may be even more important for understanding intra-individual differences revealed at 13 Soutschek and colleagues [59] have suggested that the brain regions underlying self-control mechanisms involved in individual decision dilemmas (e.g., trading off impulsive short vs. restrained long-term goals) are also underlying decisions in social dilemmas (e.g., trading off exploitative and individually beneficial vs. cooperative and mutually beneficial goals).…”
Section: Discussionsupporting
confidence: 77%
“…Also puzzling is how, under dilemma conditions, "extreme" behavior is commonly chosen, despite available options for more moderate behavior. Others have also found anomalous effects on behavior by altering the set of available options (e.g., [2,3]) or by manipulating the strength and decay rate (or memory) of recent emotions (e.g., [4,5]). …”
Section: Self-control In Decision Dilemmasmentioning
confidence: 99%
See 2 more Smart Citations
“…give them power over the hearing aid, supporting research by [ [20][21][22][23]. According to one participant, having this control will reduce the need to articulate preferences for settings to an audiologist, whom he relies on to interpret them.…”
Section: Using Software As a Control Mechanismmentioning
confidence: 68%